2009
DOI: 10.1128/jcm.00630-09
|View full text |Cite
|
Sign up to set email alerts
|

Reemergence of Enterovirus 71 in 2008 in Taiwan: Dynamics of Genetic and Antigenic Evolution from 1998 to 2008

Abstract: In recent years, enterovirus 71 (EV71) has been a cause of numerous outbreaks of hand-foot-and-mouth disease, with severe neurological complications in the Asia-Pacific region. The reemergence in Taiwan of EV71 genotype B5 in 2008 resulted in the largest outbreak of EV71 in Taiwan in the past 11 years. Phylogenetic analyses indicated that dominant genotype changes from B to C or C to B occurred at least three times between 1986 and 2008. Furthermore, antigenic cartography of EV71 by using neutralization tests … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

10
206
2

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 174 publications
(218 citation statements)
references
References 54 publications
(59 reference statements)
10
206
2
Order By: Relevance
“…3D). This region at the 5-fold vertex represents a functional "hot spot," since these residues have been implicated in receptor binding and have been shown to determine virus virulence and affect positive selection (4,(10)(11)(12)18).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…3D). This region at the 5-fold vertex represents a functional "hot spot," since these residues have been implicated in receptor binding and have been shown to determine virus virulence and affect positive selection (4,(10)(11)(12)18).…”
Section: Resultsmentioning
confidence: 99%
“…However, EV71 infection may lead to severe neurologic diseases, including meningitis, poliomyelitis-like disease, and fatal cases of encephalitis (3). Since first reported, EV71 has been implicated in an increasing number of outbreaks throughout the world and is now classified as an emerging infectious disease with pandemic potential (4,5). A thorough structural and mechanistic understanding of the virus and its interactions with host cells will support efforts to develop antiviral therapies, and we focus here on establishing a structural basis for this knowledge.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…It was previously reported that the reemergence of B5 genotype resulted in a large EV71 outbreak in Taiwan, and detected B5 strains were shown to possess genetic and antigenic diversity compared to previously circulating strains (16). Similarly, the emer-gence of strains with different antigenicity might have been involved in the worldwide occurrence of EV68 outbreaks in recent years.…”
Section: H Uman Enterovirus 68 (Ev68) (Species Human Enterovirus D;mentioning
confidence: 99%
“…There were reports of shifts of sub-genotype dominance in Taiwan and Japan, from B-sub-genotypes to C-sub-genotypes [22,23]. In more recent years, three new genotypes were discovered; one in India (designated as genotype D), one in Central Africa (designated as genotype E) and another from Madagascar (designated as genotype F) by sequencing the VP1 and VP2 regions of clinical isolates [24].…”
Section: Epidemiologymentioning
confidence: 99%